Penegakan Hukum Korupsi Dana Desa di Provinsi Sulawesi Selatan - Amir Amir; Auliah Ambarwati; Ardiyanti Aris (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This journal aims to find out and analyze law enforcement, the volume of corruption, and the consequences of village fund corruption since it was disbursed in South Sulawesi Province from 2017 until now. This type of research is normative juridical research using a conceptual approach to legislation assisted by primary, secondary, and tertiary legal materials, which will be described, described, and analyzed using the theory of corruption. The results of this study are about law enforcement, an illustration of the high number of cases of corruption in village funds in South Sulawesi Province, which so far, before the transfer of village funds by the central government to the regions, there were rare cases of corruption in village funds which were charged with the Corruption Crime Act Number 31 of 1999 which changed into Law Number 20 of 2001 concerning the Eradication of Corruption Crimes which should, for the distribution of funds to be on target, proposed by the researchers aimed at the absorption of village funds budgets must be monitored, planned properly so that the absorption is effective and efficient for the welfare of rural communities in South Sulawesi Province.